Skeletal biology of human populations between classical and post-classical times in Italy: The evidence of dental enamel hypoplasia - Saraka, Erwin Mansyur Ugu (2020)
Abstract: Linear enamel hypoplasia (LEH) occurs during tooth formation and shows systemic physiological stress caused by various factors, including; malnutrition, congenital genetic defects and infections. It can be identified as pits or grooves, that are mostly visible on the labial side of the teeth crowns. For this work, all the material analyzed come from skeletal remains of classical and post-classical populations from Italy (IV - VIII century AD); it pertains to the cemeteries of Povegliano Veronese (POV), in Verona, Northern Italy, and Selvicciola (SLV) in Viterbo, Central Italy, now stored in the Museum of Anthropology "Giuseppe Sergi" of the Sapienza University of Rome. Linear Enamel Hypoplasia data collected from POV include 56 adult individuals (namely 23 males, 22 females and 11 undetermined), while at SLV, the total population of 120 individuals consists of 29 males, 14 females, 32 undetermined and the rest are infants, children and sub adults. The aim of this research is to provide an overview of the frequency of enamel hypoplasia, the earliest developmental age estimates for the formation of dental enamel hypoplasia as well as the nutritional status in comparing the two populations. Identification, description and assessment through macroscopic analysis were used to investigate the timing of growth of the disturbance. Data obtained from measurements using standardized methods were processed by statistical analysis using a regression equation for estimation of the age of occurrence. The frequency of individuals with LEH at POV is around 41%, while at SLV 37.5% of the population was affected. The age of occurrence of LEH at POV ranges between 1.0/1.5 and 7.1/7.5 years and reaches the peak in the age classe of 2.1/2.5. On the other hand, LEH at SLV is found between 0.0/0.5 and 5.6/6.0 age at death with a peak around 2.1/2.5 and 2.6/3.0. Comparison of LEH chronological distribution based on sex from POV and SLV shows that LEH at POV is dominated by female with a fairly high frequency compared to male, meanwhile in SLV it is the opposite.